3D Organotypic Spinal Cultures: Exploring Neuron and Neuroglia Responses Upon Prolonged Exposure to Graphene Oxide - Musto, Mattia; Rauti, Rossana; Rodrigues, Artur Filipe; Bonechi, Elena; Ballerini, Clara; Kostarelos, Kostas; Ballerini, Laura (Frontiers in Systems Neuroscience, 2019)
Graphene-based nanomaterials are increasingly engineered as components of biosensors, interfaces or drug delivery platforms in neuro-repair strategies. In these developments, the mostly used derivative of graphene is graphene oxide. To tailor the safe development of graphene oxide nanosheets, we need to model in vitro tissue responses, and in particular the reactivity of microglia, a sub-population of neuroglia that acts as the first active immune response, when challenged by graphene oxide. Here, we investigated central nervous system tissue reactivity upon long-term exposure to graphene oxide nanosheets in 3D culture models. We used the mouse organotypic spinal cord cultures, ideally suited for studying long-term interference with cues delivered at controlled times and concentrations. In cultured spinal segments, the normal presence, distribution and maturation of anatomically distinct classes of neurons and resident neuroglial cells are preserved. Organotypic explants were developed for two weeks embedded in fibrin glue alone or presenting graphene oxide nanosheets at 10, 25 and 50 µg/mL. We addressed the impact of such treatments on premotor synaptic activity monitored by patch clamp recordings of ventral interneurons. We investigated by immunofluorescence and confocal microscopy the accompanying glial responses to graphene oxide exposure, focusing on resident microglia, tested in organotypic spinal slices and in isolated neuroglia cultures. Our results suggest that microglia reactivity to accumulation of graphene oxide flakes, maybe due to active phagocytosis, may trimm down synaptic activity, although in the absence of an effective activation of inflammatory response and in the absence of neuronal cell death.